No Evidence of an Association Between Efavirenz Exposure and Suicidality Among HIV Patients Initiating Antiretroviral Therapy in a Retrospective Cohort Study of Real World Data. Issue 3 (January 2016) - Nkhoma, Ella T.; Coumbis, John; Farr, Amanda M.; Johnston, Stephen S.; Chu, Bong Chul; Rosenblatt, Lisa C.; Seekins, Daniel; Villasis-Keever, Angelina
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Recently, published studies have reported conflicting results regarding the association between efavirenz exposure and the risk of suicidality among patients with human immunodeficiency virus. The objective of this analysis was to compare the rate of suicidality among patients initiating efavirenz-containing versus efavirenz-free antiretroviral (ARV) regimens. This retrospective cohort study used US administrative claims data for commercially and Medicaid-insured individuals for the years 2006 to 2013. ARV-naive patients aged ≥12 years initiating an efavirenz-containing or efavirenz-free ARV regimen with ≥6 months of continuous insurance enrollment prior to ARV initiation were selected. The primary outcome was suicidality, defined as the occurrence of any medical claim with a diagnosis code for suicidal ideation or an inpatient or emergency department medical claim for suicide attempt. Unadjusted incidence rates were calculated and propensity score-adjusted hazard ratios were estimated to account for differences in patient characteristics. There were 19, 983 patients (efavirenz-containing, n = 11, 187; efavirenz-free, n = 8796) in the commercial database and 5154 patients (efavirenz-containing, n = 2224; efavirenz-free, n = 2930) in the Medicaid database. Unadjusted incidence rates (95% confidence interval [CI]) of suicidality per 1000 person-years were: commercial, efavirenz-containing (3.3 [2.4–4.4]), efavirenz-free (4.0 [2.7–5.8]); Medicaid, efavirenz-containing (25.7 [18.8–34.4]), efavirenz-free (40.6 [31.9–50.9]). In propensity score-adjusted analyses, efavirenz use was not associated with suicidality: adjusted hazard ratio (95% CI) of suicidality compared with efavirenz-free regimen, commercial, 1.029 (0.636–1.665); Medicaid, 0.902 (0.617–1.319). This analysis found no conclusive evidence of an increased risk of suicidality among patients initiating an efavirenz-containing ARV regimen. However, channeling bias may exist even after adjusting for measured patient characteristics.